1997
DOI: 10.1017/s0016756897007590
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic data on major Variscan strike-slip faults and shear zones in the Polish Sudetes, northeast Bohemian Massif

Abstract: The still highly disputable terrane boundaries in the Sudetic segment of the Variscan belt mostly seem to follow major strike-slip faults and shear zones. Their kinematics, expected to place important constraints on the regional structural models, is discussed in some detail. The most conspicuous is the WNW–ESE Intra-Sudetic Fault Zone, separating several different structural units of the West Sudetes. It showed ductile dextral activity and, probably, displacement magnitude of the order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 18 publications
(35 reference statements)
2
83
0
1
Order By: Relevance
“…It is lo cated north-east of the vil lage of Janowice Wielkie (Fig. 1), im me di ately south of the Intra-Sudetic Fault, one of the ma jor Variscan geolog i cal bor ders in the north-east part of the Bo he mian Mas sif, in Cen tral Eu rope (Aleksandrowski et al, 1997).…”
Section: Geological Setting and Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is lo cated north-east of the vil lage of Janowice Wielkie (Fig. 1), im me di ately south of the Intra-Sudetic Fault, one of the ma jor Variscan geolog i cal bor ders in the north-east part of the Bo he mian Mas sif, in Cen tral Eu rope (Aleksandrowski et al, 1997).…”
Section: Geological Setting and Previous Workmentioning
confidence: 99%
“…The peridotite is sur rounded by low-grade metabasic rocks ("striped metabasites"), be long ing to the Kowary Unit of the Rudawy Janowickie Com plex (Aleksandrowski et al, 1997), sur round ing the Variscan Karkonosze gran ite to the east and north-east. Popiel Hill is sit u ated within ca.…”
Section: Geological Setting and Previous Workmentioning
confidence: 99%
“…The onset of activity of the WNW to NW-striking dextral ductile shear zones in the Variscides is dated as Late Devonian-Viséan (e.g., Aleksandrowski et al 1997, Matte et al 1986, i.e., before the formation of the Late Carboniferous extensional basins. Later activity occurred at < 295 Ma, in late Stephanian to early Permian, with dextral motions interpreted by Pitra et al (1999), and putative sinistral kinematics suggested by Mattern (2001).…”
Section: Wnw-to Nw-trending Faults: the Labe And Sudetic Fault Groupsmentioning
confidence: 99%
“…We discuss the details of mantle evolution recorded in the xenoliths and comment on its significance to the overall characteristics of the Lower Silesian mantle domain of the European Variscan orogen. U p p e r E l b e F a u l t Z o n e O d r a F a u l t Z o n e I n t r a -S u d e t i c F a u l t Z o n e The Pilchowice basanite is located directly on the IntraSudetic Fault (ISF)-a major Variscan NW-SE trending, long-living (Devonian-Carboniferous, Don 1984 or Devonian-Permian; Aleksandrowski et al 1997) dislocation transecting whole the Sudetes. In the vicinity of Pilchowice the ISF separates Karkonosze-Izera Block (represented by gneisses) from the mica schists of Kaczawa Complex (Fig.…”
Section: Introductionmentioning
confidence: 99%